Effect of coolant plate geometry and material in a freshwater production system: an experimental study - Bahar, Rubina; Hawlader, Mohammad Nurul Alam; Mohamed Ariff, Tasnim Firdaus (2014)
Channeled coolant plates have been playing an important role in the field of various heat transfer applications. Due to the “fin effect”, the overall heat transfer area increases and thus the amount of energy transfer enhances. In this study, effect of a specially designed coolant plate has been used to observe its effect on heat transfer during condensation in a freshwater production system. Compared to a flat coolant plate, the freshwater production enhanced maximum up to 50% for a coolant temperature of 25° C with this channeled plate. In addition, the plate material was varied and production enhancement was observed for the higher conductive material.